Numerical simulations and mathematical models in laser welding: a review based on physics and heat source models - Jiménez-Xamán, M.; Hernández-Hernández, M.; Tariq, Rasikh; Landa-Damas, Saulo; Rodríguez-Vázquez, M.; Aranda-Arizmendi, A.; Cruz-Alcantar, P. (Frontiers in Mechanical Engineering, 2024)
The dominant phenomenon in laser welding processes is heat transfer by conduction, making it crucial to gain insights into energy distribution within the heat-affected region, including the melt pool.Thermal analysis enables the description of thermo-mechanical, metallurgical aspects, and also addresses studies related to fluid flow and energy transfer. As research in welding processes has advanced, these models have evolved. This is why it is now efficient to employ computational modeling techniques as it allows us to analyze the behavior of laser welding during the process. This underlines the importance, in this work that has carried out an exhaustive theoretical literature review with the objective of classifying and describing the numerical simulations of laser welding based on the physics involved. In that sense, the mathematical models and strategies used in laser welding are explored in a general way. Therefore, two types of laser welding by conduction and deep penetration are defined from this point, they are categorized according to the phenomena involved in Model Heat Conduction and Model Integral Multiphysics. This comprehensive review article serves as a valuable resource for higher education students by providing a structured and detailed exploration of laser welding and its mathematical modeling. By classifying and describing numerical simulations based on the physics involved, it offers a framework for students to understand the complexities of this field.Additionally, this innovative approach to organizing and presenting research contributes to educational innovation by facilitating a more efficient and effective learning experience, helping students acquire the knowledge and research skills necessary for advancements in the laser welding domain.